ANALISIS EFISIENSI PENGENDALIAN BIAYA KUALITAS PADA AKSAN BAKERY MANADO - Adam, Fitriayani; Manossoh, Hendrik; Pinatik, Sherly (Universitas Sam Ratulangi, 2016)
Quality being the competitiveness of the most important for the company's products and also because the quality has been the hope and desire of everyone, especially the consumer. Customers are not going to focus on a product / service only in terms of price but in good quality inherent in the product or service. Viewed from the importance of the quality of products, each company needs to spend quality, cost of quality is the cost refers to the cost incurred to prevent or expenses incurred as a result of producing a quality product. Efforts to improve the quality of the product will not run without the cost of quality control to overcome the problems faced by the company, where quality control can help the company determine the feasibility of the quality of products based on control limits have been set. This study aims to see how the cost of quality control and to analyze the efficiency of the implementation cost of quality control conducted by Aksan Bakery in Manado. Analysis of the data used is descriptive analysis with qualitative approach and using methods of presentation quality cost ratio analysis to assess the efficiency cost of quality. Based on analysis of the cost of quality control conducted by the company it appears that the cost of quality control conducted by the company do not meet the quality standards that have been set at 2.5% of sales, for the cost of quality issued by the company is greater than a predetermined quality standards, namely amounting to 13.89% of sales. This may imply that the cost of quality control has not been carried out efficiently. Keywords : Efficiency , Cost of Quality